Identification, quantification, spatiotemporal distribution and genetic variation of major latex secondary metabolites in the common dandelion (Taraxacum officinale agg.). (July 2015) - Huber, Meret; Triebwasser-Freese, Daniella; Reichelt, Michael; Heiling, Sven; Paetz, Christian; Chandran, Jima N.; Bartram, Stefan; Schneider, Bernd; Gershenzon, Jonathan; Erb, Matthias
Graphical abstract: Common dandelion latex contains three highly concentrated and conserved classes of secondary metabolites, each of which account for over 5% latex fresh mass: phenolic inositol esters (PIEs), triterpene acetates (TritAc), and the sesquiterpene lactone taraxinic acid β-d -glucopyranosyl ester (TA-G). Highlights: We characterized the major secondary metabolites of dandelion latex. Terpene acetates and lactones as well as phenolic inositols made up 18% fresh mass. Concentrations were highest in the roots of older plants. The different latex secondary metabolites were co-regulated. Genetic conservation and bioactivity suggest biological relevance. Abstract: The secondary metabolites in the roots, leaves and flowers of the common dandelion ( Taraxacum officinale agg.) have been studied in detail. However, little is known about the specific constituents of the plant's highly specialized laticifer cells. Using a combination of liquid and gas chromatography, mass spectrometry and nuclear magnetic resonance spectrometry, we identified and quantified the major secondary metabolites in the latex of different organs across different growth stages in three genotypes, and tested the activity of the metabolites against the generalist root herbivore Diabrotica balteata . We found that common dandelion latex is dominated by three classes of secondary metabolites: phenolic inositol esters (PIEs), triterpene acetates (TritAc) and the sesquiterpene lactone taraxinic acid β-d -glucopyranosyl ester (TA-G). Purification and absolute quantification revealed concentrations in the upper mg g −1 range for all compound classes with up to 6% PIEs, 5% TritAc and 7% TA-G per gram latex fresh weight. Contrary to typical secondary metabolite patterns, concentrations of all three classes increased with plant age. The highest concentrations were measured in the main root. PIE profiles differed both quantitatively and qualitatively between plant genotypes, whereas TritAc and TA-G differed only quantitatively. Metabolite concentrations were positively correlated within and between the different compound classes, indicating tight biosynthetic co-regulation. Latex metabolite extracts strongly repelled D. balteata larvae, suggesting that the latex constituents are biologically active.